Fostering educational innovations in the era of global digital futures with students as partners (SaP) - Agency of university students in the Asian context (Journal of Applied Learning and Teaching, 2025)
Most studies on Students as Partners (SaP) in the literature have been found to be western-centric, highlighting a significant lack of SaP studies in Asian countries. Higher education in Hong Kong is still developing its SaP practice. This article aims to address this gap by examining how student partnership fosters education innovation in the era of global digital futures, particularly through the Redesigning Student Learning Experience in Higher Education (RSLEIHE) project scheme in the recent years in Hong Kong.Believing that meaningful and impactful student partnership relies on the student agency developed during the projects, this study discusses factors facilitating student agency development through SaP projects of the RSLEIHE scheme in an age of digital futures. The two-stage research design (including student responses on a quantitative survey and a ranking task) allowed for a comprehensive exploration of student perception of student agency levels among a diverse cohort of participants from local universities in Hong Kong.The findings revealed interesting patterns and variations in student agency across different demographic factors such as gender, level of study and academic disciplines. Notably, graduate students exhibited higher levels of agency compared with undergraduate students, while female students perceived significantly more peer support. Overall, this study emphasises the significance of support systems, trust-building, and opportunities for students to make choices in shaping the student experience.